2010
DOI: 10.1111/j.1365-2036.2010.04269.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: optimizing SVR and management of the haematological side effects of peginterferon/ribavirin antiviral therapy for HCV – the role of epoetin, G‐CSF and novel agents

Abstract: Aliment Pharmacol Ther 31, 929–937 Summary Background  Chronic hepatitis C is one of the leading causes for chronic liver disease globally. The past two decades have seen many advances in hepatitis C treatment. Despite these advances, side effects of treatment are common. Haematological complications of treatment can result in treatment cessation and suboptimal results. Recent data have suggested a role for epoetin/granulocyte colony stimulating factor (G‐CSF) in optimizing sustained virological response (SVR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…Discussing the final results of Enable 1, a phase 3, multicentre study, the authors concluded that eltrombopag increases platelet counts in these patients to levels which could enable 95% of them to initiate antiviral HCV therapy, and subsequently to maintain antiviral dosage and achieve a SVR. Similar findings are reported by McHutchison et al (2007) for patients with TCP due to HCV-related cirrhosis, and by Stasi et al (2009) and Mac Nicholas and Norris (2010). 10 However, Bussel and Pinheiro (2011) reported challenges with adherence to eltrombopag treatment due to administration-related issues (it must be taken every day apart from specific meals containing high levels of calcium).…”
Section: Haematological Abnormalitiessupporting
confidence: 71%
“…Discussing the final results of Enable 1, a phase 3, multicentre study, the authors concluded that eltrombopag increases platelet counts in these patients to levels which could enable 95% of them to initiate antiviral HCV therapy, and subsequently to maintain antiviral dosage and achieve a SVR. Similar findings are reported by McHutchison et al (2007) for patients with TCP due to HCV-related cirrhosis, and by Stasi et al (2009) and Mac Nicholas and Norris (2010). 10 However, Bussel and Pinheiro (2011) reported challenges with adherence to eltrombopag treatment due to administration-related issues (it must be taken every day apart from specific meals containing high levels of calcium).…”
Section: Haematological Abnormalitiessupporting
confidence: 71%
“…However, in this study, PSE prior to starting the combined therapy did not progress the adherence to ribavirin. Recently, erythropoietic agents are shown to be effective in treating anemia, preventing ribavirin dose reduction, and improving patients' quality of life during the combined therapy (25). Hereafter, eryhthropoietic agents will be expected to improve and prevent anemia during the combined therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Repeatedly, individual RBV dose and pharmacokinetic (Pk) exposure have been found to be consistent determinants of treatment-associated anemia, and recommendations on dose reduction have been released in order to mitigate the impact of RBV on the severity of anemia (Aguilar Marucco et al, 2008;D'Avolio et al, 2012a;Kubota et al;Lindahl et al, 2004;Mac Nicholas and Norris;McHutchison et al, 2006).…”
Section: Introductionmentioning
confidence: 99%